PENGARUH METODE OUTDOOR STUDY TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPAS DI KELAS IV SD NEGERI 158501 SIBULUAN - Pasaribu, Stela Octavia; Theresia, Monica; Sabri, Sabri; Nasution, Sartika Rati Asmara (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This research aims to determine the effect of using the outdoor study method on social studies learning outcomes regarding norms and customs in my area, class IV at SD Negeri 158501 Sibuluan. The method used is quantitative experimental research using a one group pretest and posttest design. The subjects in this research were 20 students in class IV B of SD Negeri 158501 Sibuluan. The data collection technique uses a test in the form of 10-item multiple choice questions, 5 questions and 5 questions essay. Manual data analysis techniques include Normality Test, Homogeneity Test, Hypothesis Test . From the results of observations made on the homeroom teacher in class IV B of SD Negeri 158501 Sibuluan through indicators by submitting 23 statement items, an average score of 89.16 was obtained. If the assessment criteria were consulted, the score was in the "Very Good" category. Regarding student learning outcomes after using the outdoor study method, an average score of 75 was given as "good". To see the effect of the outdoor study method on learning outcomes, it can be seen from the calculations carried out to obtain tcount = 5.91. When compared with ttable at a 95% confidence level or 5% error rate with degrees of freedom (dk) = N – 1 = 20 – 1 = 19, ttable is 2,093. If the value of tcount = 5.91 is compared with ttable= 2.093 then it can be seen that tcount is greater than ttable, namely 5.91>2.093. Thus, it can be concluded that there is an influence of the use of outdoor study methods on the learning outcomes of students in science and science subjects in class IV of SD Negeri 158501 Sibuluan.